Leveraging the Value of Land and Landside Access to Fund Port Infrastructure in Texas. Issue 11 (December 2018) - Aldrete, Rafael M.; Kruse, Carl James; Salgado, David; Vadali, Sharada R.; Mudgal, Abhisek; Villa, Juan Carlos; Cornejo, Lorenzo E.; Bae, Deog Sang
This paper introduces port authority transportation reinvestment zones (TRZs), a funding tool created by the Texas Legislature to help fund long-term economic development port projects. TRZs were first introduced in Texas in 2007 as a tool to allow county and municipal governments to raise funds to help pay for transportation improvements using the property tax mechanism. Since then, the legislation has been amended to include other transportation modes, such as transit, rail, and parking facilities. Amendments passed in 2013 introduced the concept of port authority TRZ, which expanded authorized use of the tool to the state's port authorities and navigation districts. Most of the existing funding tools available to Texas ports focus on the development of infrastructure within port property. Port authority TRZs complement existing funding sources by providing a funding tool flexible enough to fund port projects both inside and outside port property. Port authorities can take advantage of the TRZ concept to join forces with neighboring local governments and the Texas Department of Transportation to fund landside transportation enhancements that improve port accessibility and the regional economy. Currently, there are four active port authority TRZs in the following locations: Port of Beaumont, Port of Port Arthur, Port of Brownsville, and Sabine-Neches Navigation District. This paper summarizes the legal framework of port authority TRZs, describes the role that these TRZs play in port funding and finance, and presents highlights of the port authority TRZs that have already been established throughout the state.